Solar Occultation FTIR Spectrometry at Mars for Trace Gas Detection: A Sensitivity Study. Issue 5 (28th May 2019) - Toon, Geoffrey C.; Liebe, Carl Christian; Nemati, Bijan; Harris, Ian; Kleinböhl, Armin; Allen, Mark; Hipkin, Vicky; Drummond, Jim; Soucy, Marc‐André; Yung, Yuk L.; Zeng, Zhao‐Cheng; Wunch, Debra; et al.
Abstract: A sensitivity study has been performed to estimate detection limits of various atmospheric trace gases achievable by a Mars‐orbiting solar occultation Fourier transform infrared (FTIR) spectrometer. This was accomplished by first computing realistic limb transmittance spectra based on a model (T, P, VMR, and dust profiles) of the Mars atmosphere and adding appropriate noise and systematic errors based on assumed instrument design/configuration/performance. We then performed spectral fits to the resulting synthetic spectra to derive slant column abundances and their uncertainties. A profile retrieval was performed to infer limits of detection. This methodology was applied to a Mars‐orbiting FTIR solar occultation spectrometer covering the 850–4, 300 cm −1 spectral region at 0.025‐cm −1 resolution. We conclude that most gases can be retrieved with a single‐occultation sensitivity of 20–100 ppt. But this sensitivity varies considerably with the dust loading, especially for gases whose strongest absorption bands are toward higher wavenumbers where scattering is large. We conclude that for CH4, the ν 4 band centered at 1, 305 cm −1, despite being more than 2 times weaker than the ν 3 band centered at 3, 015 cm −1, offers better sensitivity due to its close spectral proximity to the dust extinction minimum. We also conclude that for the purpose of CH4 detection, a high‐resolution (0.025 cm −1 ) broadband instrument would have a substantial advantage over a medium‐resolution (0.15 cm −1 ) instrument, despite the latter having a much larger signal‐to‐noise ratio. Plain Language Summary: We have estimated whether an infrared spectrometer might have enough sensitivity to measure minute amounts of gases (e.g., CH4, N2 O, HCN, and OCS) in the Martian atmosphere that might arise due to life or volcanic activity. We conclude that by viewing the Sun at sunset and sunrise, many gases would be detectable at the 20–100 ppt level which would reduce current upper limits of several gases, some by factors of more than a hundred (e.g., N2 O). But airborne dust is a major impediment to detecting gases in the lowest few kilometers of the atmosphere, close to their likely sources. Key Points: The solar occultation technique provides high (ppt) sensitivity to many atmospheric trace gases, due to the long atmospheric paths and the brightness of the Sun Dust extinction is a major obstacle in the lower Mars atmosphere to detecting trace gases without strong absorption bands at wavenumbers less than 2, 400 cm −1 or for spectrometers without coverage at wavenumbers less than 2, 400 cm −1 High spectral resolution (0.025 cm −1 ) offers significant advantages over medium‐resolution spectrometers (0.15 cm −1 ) for detecting trace gases (e.g., CH4 ) whose absorptions are overlapped by much stronger interfering absorptions (e.g., from CO2 or H2 O)